2017
DOI: 10.11648/j.jgo.20170501.12
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Heterotopic Pregnancy: A Case Report

Abstract: Heterotopic pregnancy is a pathological form of biovular dizygotic twin pregnancy. This is a rare disease, but its incidence has increased sharply in recent years due to the development of medically assisted procreation and the resurgence of pelvic infections. Diagnosis and therapeutic management of heterotopic pregnancy are essential to improve maternal prognosis and proper conduct of the intrauterine pregnancy. The authors report a new advanced heterotopic pregnancy in a woman treated for infertility. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…TVS now showed some free fluid in the cul-de-sac. Similarly, as noted by Mohamed,4 patients often present early asymptomatically with some signs such as minimal bleeding. Later as the ectopic pregnancy progresses, they show further clinical indications of coexisting intrauterine pregnancy such as the classic triad of amenorrhoea, vaginal bleeding and pelvic pain 4.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…TVS now showed some free fluid in the cul-de-sac. Similarly, as noted by Mohamed,4 patients often present early asymptomatically with some signs such as minimal bleeding. Later as the ectopic pregnancy progresses, they show further clinical indications of coexisting intrauterine pregnancy such as the classic triad of amenorrhoea, vaginal bleeding and pelvic pain 4.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, as noted by Mohamed,4 patients often present early asymptomatically with some signs such as minimal bleeding. Later as the ectopic pregnancy progresses, they show further clinical indications of coexisting intrauterine pregnancy such as the classic triad of amenorrhoea, vaginal bleeding and pelvic pain 4. The finding of free fluid in the pelvis combined with the adnexal mass now raised the suspicion of HP which is extremely rare to begin with and an even rarer occurrence in a spontaneous conception.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…3,4 Risk factors such as sexual transmited infections, tubal surgery, and also ovulation induction with gonadotropin and clomiphene citrate could also increase the incidence of heterotopic pregnancy. 5,6 This confirms that the significance of detection of risk in pregnant woman in order to increase awareness of diagnosing this rare condition. In this written case, there were no risk factors, in other words it is concluded that this case is a spontaneus HP, which is a very rare condition.…”
Section: Discussionsupporting
confidence: 70%
“…While more than 50% of HP cases are asymptomatic, abdominal pain, adnexal mass, peritoneal irritation, and also an enlarged uterus could also be the manifestation of heterotopic pregnancy. 6,7 Early and proper diagnosis of heterotopic pregnancy could significantly reduce the patient's mortality rate. 7 This becomes a challenging problem for Obstetricians in achieving an accurate diagnosis by facing obscure clinical symptoms from patients, in order to reduce the mortality rate.…”
Section: Discussionmentioning
confidence: 99%